Magnetic properties of Proxima Centauri b analogues. (March 2018) - Zuluaga, Jorge I.; Bustamante, Sebastian
Abstract: The discovery of a planet around the closest star to our Sun, Proxima Centauri, represents a quantum leap in the testability of exoplanetary models. Unlike any other discovered exoplanet, models of Proxima b could be contrasted against near future telescopic observations and far future in-situ measurements. In this paper we aim at predicting the planetary radius and the magnetic properties (dynamo lifetime and magnetic dipole moment) of Proxima b analogues (solid planets with masses of ∼ 1 − 3 M ⊕, rotation periods of several days and habitable conditions). For this purpose we build a grid of planetary models with a wide range of compositions and masses. For each point in the grid we run the planetary evolution model developed in Zuluaga et al. (2013). Our model assumes small orbital eccentricity, negligible tidal heating and earth-like radiogenic mantle elements abundances. We devise a statistical methodology to estimate the posterior distribution of the desired planetary properties assuming simple lprior distributions for the orbital inclination and bulk composition. Our model predicts that Proxima b would have a mass 1.3 ≤ M p ≤ 2.3 M ⊕ and a radius R p = 1.4 − 0.2 + 0.3 R ⊕ . In our simulations, most Proxima b analogues develop intrinsic dynamos that last for ≥ 4 Gyr (the estimated age of the host star). If alive, the dynamo of Proxima b have a dipole moment ℳ dip > 0.32 ÷ 2.9 × 2.3 ℳ dip, ⊕ . These results are not restricted to Proxima b but they also apply to earth-like planets having similar observed properties. Highlights: We estimate magnetic properties of Proxima Centauri b planetary analogues. Radius, magnetic dipole moment and dynamo lifetime are predicted for Proxima b. For this purpose a grid of thermal evolution models (different masses and compositions) is computed. A statistical method resembling Bayesian Hierarchical Models is used.